The Voluntary Nature of Decision-Making in Addiction: Static Metaphysical Views Versus Epistemologically Dynamic Views - Racine, Eric (Bioethics, 2017)
The degree of autonomy present in the choices made by individuals with an addiction, notably in the context of research, is unclear and debated. Some have argued that addiction, as it is commonly understood, prevents people from having sufficient decision-making capacity or self-control to engage in choices involving substances to which they have an addiction. Others have criticized this position for being too radical and have counter-argued in favour of the full autonomy of people with an addiction. Aligning ourselves with middle-ground positions between these two extremes, we flesh out an account of voluntary action that makes room for finer-grained analyses than the proposed all-or-nothing stances, which rely on a rather static metaphysical understanding of the nature of the voluntariness of action. In contrast, a dynamic concept of voluntary action better accounts for varying levels of voluntariness of the person with an addiction which takes into consideration internal (e.g. cravings) and external (e.g. perceptions of degrees of freedom related to different options) determinants of choice. Accordingly, like other components of autonomous choices such as level of information, voluntariness can fluctuate. Therefore, there are important implications for research and clinical ethics in matters of consent, recruitment, and therapeutic approaches. Overall, our proposal is inspired by a pragmatist understanding of voluntary action, notably with respect to how voluntariness is both informed by actions and experiences that shape one's view of the world.